âThe Next Dermatological Tool is Getting Purchased Directly By The Patient â The Diagnostic Appâ - Kalsi, Ishar Alexander (Journal of Medical Biomedical and Applied Sciences, 2018)
Thanks to those Ã¢â¬ÅcubesÃ¢â¬ on our smartphones, we now have the ability to book our summer holidays and have dinner delivered to our homes from the back seat of a vehicle summoned with an app. Apps are the driving tool behind our increasingly self-empowered lives. Where do the latest dermatology apps fit into this app craze?